ISSUES OF FORMATION OF HUMAN EDUCATION AND THINKING IN HADITHS AND NARRATIVES OF IMAM AL-BUKHARY - Murodov Shuhrat Sharipovich (Western European Studies, 2024)
In this article, Imam al-Bukhari's hadiths and narrations discuss human education, the enrichment of youth minds with universal cultural ideas, and family issues in the formation of the thinking of the next generation, as well as mutual love, trust, cooperation and mutual understanding between parents. it is about respect, sincerity of relations
Keywords: World civilization; scientific research center; hadith